Clinical guidance for peripartum management of patients with hereditary thrombophilia. Issue 9 (24th June 2021) - Kobayashi, Takao; Morishita, Eriko; Tsuda, Hiroko; Neki, Reiko; Kojima, Tetsuhito; Ohga, Shouichi; Ochiai, Masayuki; Adachi, Tomoko; Miyata, Toshiyuki
Abstract: Hereditary thrombophilia is a condition in which individuals are susceptible to the formation of thrombi due to a hereditary deficiency in anticoagulant factors, antithrombin (AT), protein C (PC), or protein S (PS). Many Japanese thrombophilia patients have PS deficiency, especially PS p.K196E (also called as PS Tokushima), which is exclusive to the Japanese population, and thrombosis sometimes occurs during pregnancy. At present, no management guidelines for pregnancy and delivery in thrombophilia patients have been developed. The Study Group for Hereditary Thrombophilia, one of the research groups of blood coagulation abnormalities in the Research Program on Rare and Intractable Diseases supported with the Research Grants of the Ministry of Health, Labour and Welfare Science, has therefore developed this clinical guidance to provide healthcare workers with necessary information on safe pregnancy, parturition and neonatal management, adopting a format of responses to seven clinical questions (CQ). At the end of each answer, the corresponding Recommendation Level (A, B, C) is indicated.